PENGARUH IKLIM ORGANISASI TERHADAP LOYALITAS KARYAWAN PADA HOTEL RATU MAYANG GARDEN PEKANBARU - Mursita, Windhi; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Ratu Mayang Garden Hotel Pekanbaru is a 3 star hotel ( *** ) in Pekanbaru and located Jl . Sudirman no. 11 Pekanbaru . The implementation of organizational climate is expected to add to the loyalty of employees at Hotel Ratu Mayang Graden Pekanbaru . Organizational Climate implementation Ratu Mayang Garden Hotel Pekanbaru ie Organizational Structure , standards - standards , responsibility , respect , support and commitment In this research methodology is descriptive and quantitative with SPSS , where samples were used that employees Ratu Mayang Garden Hotel Pekanbaru and as a source of information is the Marketing Manager . To determine the sample using slovin test , sampling with accidental sampling method . The technique of collecting data through interviews and questionnaires . The analysis is a statistical analysis with SPSS version 20. The result of the calculation is the determination coefficient of 0.493 . This means that organizational climate significantly influence employee loyalty at 49.3 % . Keywords : organizational climate , employee loyalty , Organizational Structure